Targets, Predictability, and Performance - Peñaranda, Francisco; Wu, Liuren (Management Science, 2022)
We study market-timing strategies on a given portfolio to achieve a particular risk or return target. Targeting a constant risk level leads to increasing investment at better investment opportunities, whereas targeting a constant expected return does the opposite. Theoretical and numerical analysis shows that within the usual ranges of investment opportunities, risk targeting generates better unconditional performance than return targeting across a wide range of metrics. Empirical analysis with commonly constructed stock portfolios further highlights the practical infeasibility of return targeting due to the inherently low out-of-sample predicting power. By contrast, risk targeting tends to enhance unconditional stability and performance. This paper was accepted by Kay Giesecke, finance.